Media Studies and Politics in Indonesia: a Systematic Literature Review - Saputra, Gemilang Bayu Ragil; Nurliana; Sari, Dyah Fitria Kartika; Kudratullah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This study aims to systematically map the themes, trends, and gaps in media and political studies in Indonesia between 2020 and 2025. The method used was a systematic literature review (SLR) guided by the PRISMA framework. The dataset was collected through the Scopus/ScienceDirect database using specific keywords. The initial data collection yielded 98 entries. After screening and eligibility assessment, the clean data yielded 32 entries. The dataset was analysed using the bibliometrix tool in RStudio. The analysis showed that the phrase